2009
DOI: 10.4037/ajcc2009523
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mechanical Chest Percussion on Intracranial Pressure: A Pilot Study

Abstract: Background Treatment of brain injury is often focused on minimizing intracranial pressure, which, when elevated, can lead to secondary brain injury. Chest percussion is a common practice used to treat and prevent pneumonia. Conflicting and limited anecdotal evidence indicates that physical stimulation increases intracranial pressure and should be avoided in patients at risk of intracranial hypertension.Objectives To explore the safety of performing chest percussion for patients at high risk for intracranial hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17] In contrast, administration of oral care by using either manual or electric toothbrushes among intubated neurologically impaired patients does not result in significant increases in ICP. 18,19 Similarly, Olson et al, in a series of 3 articles, 5,20,21 explored the effects of chest percussion therapy on ICP, finding that such therapy does not adversely affect ICP and may be associated with lower ICP for some patients. Although these interventions are often necessary to provide adequate care for critically ill patients, as they reduce risk of ventilatorassociated pneumonia and pressure ulcers, other nursing interventions are performed with the aim of specifically decreasing ICP values.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15][16][17] In contrast, administration of oral care by using either manual or electric toothbrushes among intubated neurologically impaired patients does not result in significant increases in ICP. 18,19 Similarly, Olson et al, in a series of 3 articles, 5,20,21 explored the effects of chest percussion therapy on ICP, finding that such therapy does not adversely affect ICP and may be associated with lower ICP for some patients. Although these interventions are often necessary to provide adequate care for critically ill patients, as they reduce risk of ventilatorassociated pneumonia and pressure ulcers, other nursing interventions are performed with the aim of specifically decreasing ICP values.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Although some interventions are specifically targeted to reduce ICP, a variety of interventions may directly or indirectly affect ICP. [4][5][6][7] The impact of these interventions has not been well described. A few select studies [8][9][10] have been done to investigate statistical correlations between a specific intervention and ICP values.…”
mentioning
confidence: 99%
“…(19,20,21,23) In addition, another included study did not report any significant differences after comparing the group of patients receiving the RP maneuvers with the control group without intervention. (22) None of the studies analyzed reported significant changes in CPP before, during and/or after the RP interventions.…”
Section: Resultsmentioning
confidence: 95%
“…Only one study (22) had a control group without intervention for comparison of the results; the remaining studies provided comparisons between periods (prior to, during and after the intervention). Four of the included studies only used a single intervention session.…”
Section: Resultsmentioning
confidence: 99%
“…[3] Chest physiotherapy has conflicting data about its effect on intracranial pressure (ICP) in neurological patients with head injury. [45] Mean arterial blood pressure (BP) and central venous pressure should be monitored in order to prevent adverse events such as autonomic dysreflexia or bradycardia in the patients admitted to the neurological ICU. Coughing can further increase the risk of re-bleed in patients with cerebral bleed.…”
Section: Introductionmentioning
confidence: 99%